Legal Certainty for the Implementation of Fiduciary Guarantee in Indonesia Post-Constitutional Court Decision No. 18/PUU-XVII/2019 - Hakim, Sofyan; Shesa, Laras (Berasan: Journal of Islamic Civil Law, 2025)
Fiduciary guarantee institutions play an important role in Indonesia's financing system because they allow debtors to retain control of collateral while providing legal protection for creditors. However, in practice, the mechanism for executing fiduciary guarantees often causes problems, especially after Constitutional Court Decision No. 18/PUU-XVII/2019, which reinterpreted the executory power of fiduciary certificates. The ruling requires acknowledgment of default by the debtor or a court ruling in the event of refusal of execution. This study aims to analyze the legal certainty of fiduciary guarantee enforcement after the ruling and assess its implications for the legal relationship between creditors and debtors. This study uses a normative legal research method with a legislative and conceptual approach. Legal materials were analyzed through a literature study using systematic, historical, and teleological interpretation techniques of Law No. 42 of 1999, its implementing regulations, and relevant Constitutional Court decisions. The results of the study show that the Constitutional Court's decision has shifted the paradigm of fiduciary execution from formal legal certainty to legal certainty that is more oriented towards substantive justice. However, the absence of technical regulations regarding the form of default recognition and voluntary surrender procedures has created new uncertainties in practice. Therefore, regulatory harmonization, the development of default evidence guidelines, and the strengthening of the fiduciary administration system are necessary to ensure the fair and effective implementation of fiduciary guarantees and provide legal certainty for the parties.